Improving Teacher Performance through Strengthening Organizational Culture, Teamwork, Self-Efficacy, and Work Motivation - Ira Miranti; Soewarto Hardhienata; Widodo Sunaryo (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
The purpose of this research is to improve teacher performance through strengthening organizational culture, teamwork, self-efficacy, and work motivation. The method used in this research is quantitative, with path analysis. Then continued with SITOREM analysis to analyze the variable indicator items that affect performance. The results of this study are that there is a direct influence of organizational culture, teamwork, self-efficacy, and work motivation variables on teacher performance; there is a direct influence of organizational culture, teamwork, and self-efficacy on work motivation; there is an indirect influence of organizational culture, teamwork, and self-efficacy on teacher performance through work motivation.